DISCOURSE ANALYSIS OF BUGIS MAKASSAR CULTURE IN TARUNG SARUNG MOVIE - Salman, Elsa Claudia; Mau, Muliadi; Karnay, Sudirman; Hasana, Wa Ode Ria Ika (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
This research aims to find out how the representation of Bugis Makassar culture in Tarung Sarung movie. The research method used is discourse analysis with Stuart Hall's Representation theory approach that can be used to describe how the director represents the existing scenes. The subjects in this study are several scenes depicting Makassar Bugis culture in Tarung Sarung movie in the movie. Data were collected through observation and literature study. The results showed that Tarung Sarong movie represented various aspects of Bugis Makassar culture, including Tarung Sarong culture, wedding procession, conflict resolution method, housewarming custom, and typical food. The findings provide insight into how local culture can be articulated through film media and enrich cultural studies in the context of mass media.